The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12913-021-07388-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with dental service utilization among early elderly in Lithuania

Abstract: Background There is no recent information about dental service utilization (DSU) among elderly in Lithuania. We examined DSU and its associated factors in Lithuanian early elderly based on the Andersen’s behavioural model. Methods The cross-sectional study conducted in 2017–2019 included a nationally representative stratified sample of 370 Lithuanian early elderly aged 65–74 years (response rate of 54.5%). Information on predisposing factors (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The proportion of participants reporting the last dental visit within the last year increased in both age groups. A recent study indicated that the majority of 65-74-year-old Lithuanians needed dental treatment; however, only approximately two-thirds of them visited a dentist during the last year [Drachev et al, 2022]. The authors concluded the need for more studies to examine the barriers and facilitators to dental service utilization and to establish a national oral health program for the Lithuanian elderly emphasizing the value of regular preventive dental examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of participants reporting the last dental visit within the last year increased in both age groups. A recent study indicated that the majority of 65-74-year-old Lithuanians needed dental treatment; however, only approximately two-thirds of them visited a dentist during the last year [Drachev et al, 2022]. The authors concluded the need for more studies to examine the barriers and facilitators to dental service utilization and to establish a national oral health program for the Lithuanian elderly emphasizing the value of regular preventive dental examinations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have reported the presence of teeth as an important factor in the utilization of dental services. [29][30][31] Thus, longitudinal studies are necessary to support the causative effects between the last dental visit and complete tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found the last dental visit and several other exploratory variables to be strongly associated with the outcome of complete edentulism in our analysis, we are unable to provide strong evidence for causation. For example, previous studies have reported the presence of teeth as an important factor in the utilization of dental services 29–31 . Thus, longitudinal studies are necessary to support the causative effects between the last dental visit and complete tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that has used the Andersen model to assess socioeconomic disparities in the utilization of dental services has shown that enabling factors are key predictors [30]. Significant socioeconomic predictors included income [31][32][33][34][35][36][37], education [32,33,[35][36][37][38][39][40][41][42], wealth [32,41], dental health insurance coverage [32,35,40,43,44], and social support [28,34,43]. One study in Saudi Arabia used the Andersen model to investigate the utilization of dental services but only among children [45].…”
Section: Using the Andersen Healthcare Utilization Model As A Theoret...mentioning
confidence: 99%